Designing a Curriculum Based on Teaching Numerical Skills and Measuring its Effectiveness on the Acquisition of Mathematical Skills among a Sample of Children with Autism Spectrum Disorder in Jordan - AlKhateeb, Razan Numan; El-Zraigat , Ibrahim (Dirasat: Educational Sciences, 2020)
The main purpose of the present study was to investigate the effectiveness of designing a curriculum based on teaching numerical skills and measuring its effectiveness on the acquisition of mathematical skills among a sample of children with autism spectrum disorder in Jordan. The sample of the study consisted of 30 participants who were divided equally into two groups: an experimental group and a control group, each of which consisted of 15 participants. Two scales were developed and used; one was for acquiring mathematical skills and the other for using them. The reliability and validity of the scales were established. The researcher used ANCOVA to answer the study questions. The results showed the effectiveness of a curriculum based on teaching numerical skills and measuring its effectiveness on acquiring mathematical skills and their application among children with Autism Spectrum Disorder (ASD). The study recommended adapting a curriculum used in teaching numerical skills as well as developing a curriculum that targets advanced numerical skills for children with ASD.